HUBUNGAN ANTARA PARAMETER OSEANOGRAFI DENGAN KANDUNGAN KLOROFIL-a PADA MUSIM TIMUR DI PERAIRAN UTARA PAPUA - Hatta, Muh. (Torani Journal of Fisheries and Marine Science, 2016)
The aims of the research are to determine correlation between chlorophyll a distribution and oceanography parameter at North Papua Waters dan to identify oceanography parameter which have strong correlation on chlorophyll a distribution especially on East Monsoon. The purpose of the research provide an information about the pattern of chlorophyll a distribution and key oceanography paramater which most affected on chlorophyll a concentration at the research site. Temperature and salinity were measured using CTD (Conductivity Temperature Depth) Guildline-6000. Waters ample for measuring chemical paramater was done using Super Rosette Sampler that have Niskin Bottle that submerge with the CTD. The result showed oceanography parameter affected significantly on chlorophyll a concentration based on depth, chemical parameter. This effect was higher than other effects in particular on surface water till 200 meter depth. Keywords: oceanography parameters, chlorophyll a distribution, East Moonsoon and North Papua Waters